2011
DOI: 10.1590/s1415-47572011005000056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of common beans based on molecular markers

Abstract: A core collection of the common bean (Phaseolus vulgaris L.), representing genetic diversity in the entire Mexican holding, is kept at the INIFAP (Instituto Nacional de Investigaciones Forestales, Agricolas y Pecuarias, Mexico) Germplasm Bank. After evaluation, the genetic structure of this collection (200 accessions) was compared with that of landraces from the states of Oaxaca, Chiapas and Veracruz (10 genotypes from each), as well as a further 10 cultivars, by means of four amplified fragment length polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
1
20
1
2
Order By: Relevance
“…Genetic diversity analysis was performed among cultivars using seven microsatellite loci (BM143, BM154, BM164, BM181, BM188, GATs54, GATs91) achieved from previous reported genomic sequences (Gill-Langarica et al, 2011). Amplified PCR was obtained for each SSR according to conditions reported by Gill-Langarica et al, (2011).…”
Section: Molecular Marker Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic diversity analysis was performed among cultivars using seven microsatellite loci (BM143, BM154, BM164, BM181, BM188, GATs54, GATs91) achieved from previous reported genomic sequences (Gill-Langarica et al, 2011). Amplified PCR was obtained for each SSR according to conditions reported by Gill-Langarica et al, (2011).…”
Section: Molecular Marker Analysismentioning
confidence: 99%
“…Amplified PCR was obtained for each SSR according to conditions reported by Gill-Langarica et al, (2011). Total reaction volume included DNA (75 ng), 0.16 μM of each primer (sense and antisense), 2 μL of PCR buffer 10X, 1.5-2.5 mM of Mg (depending on each primer), 2 mM of dNTPs and 1 U of Taq DNA polymerase.…”
Section: Molecular Marker Analysismentioning
confidence: 99%
“…This variability is observed in different leaf shapes, growth habits, flower colors, but especially for seeds in terms of colors, shapes and sizes (SINGH; GEPTS; DEBOUCK, 1991). Further studies with DNA markers confirmed the high genetic diversity of common bean at the molecular level: RAPD (CARVALHO et al, 2008;KUMAR et al, 2014), microsatellites BURLE et al, 2010;PERSEGUINI et al, 2011;GIL-LANGARICA et al, 2011), AFLP (MACIEL et al, 2003;GIL-LANGARICA et al, 2011;PERSEGUINI et al, 2011), ISSR (GONZÁLEZ et al, 2005 and SNP (CORTÉS; GALEANO et al, 2012;. Furthermore, an investigation of the variability at the transcriptome level showed how domestication has shaped nucleotide and gene expression diversity (BELLUCCI et al, 2014).…”
Section: P Vulgaris Is Naturally Distributed In a Wide Area From Normentioning
confidence: 87%
“…Esses dois pools gênicos são distinguidos tanto morfologicamente (GEPTS; DEBOUCK, 1991;CHIORATO et al, 2005) quanto molecularmente (GEPTS; BLISS, 1985;GEPTS et al, 1986;KOENIG;SINGH;GEPTS, et al 1990;SINGH;BECERRA-VELÁSQUEZ;GEPTS, 1994;FREYRE et al, 1996;THOME et al, 1996;GEPTS, 2003;CHACÓN;PICKERSGILL;DEBOUCK, 2005;BLAIR et al, 2006;HANAI et al, 2007;BENCHIMOL et al, 2007;KWAK;GEPTS, 2009;GILL-LANGARICA et al, 2011).…”
Section: Origem E Domesticação De Phaseolus Vulgarismentioning
confidence: 99%
“…Os polimorfismos podem ser morfológicos, de natureza bioquímica ou molecular; neste caso, deve haver diferença na sequência de nucleotídeos do DNA, levando a um fenótipo molecular distinto (VIEIRA; VELLO; SILVA-FILHO, 2004). O conhecimento atual da estrutura populacional e da origem da domesticação do feijoeiro é baseado em estudos que utilizaram diversos marcadores moleculares, tais como: RFLPs (BECERRA-VELÁSQUEZ; GEPTS, 1994); RAPDs (FREYRE et al, 1996, BEEBE et al, 2000; AFLPs (THOME et al, 1996;BEEBE et al, 2001;PAPA;GEPTS, 2003); SSRs HANAI et al, 2007;BENCHIMOL et al, 2007;GILL-LANGARICA et al, 2011); DNA mitocondrial (KHAIRALLAH; SEARS; ADAMS, 1992) e cloroplastidial (CHACÓN et al, 2005); SNPs (MCCLEAN; LEE; MIKLAS, 2004;CHEN et al, 2010). Todavia, na maioria desses estudos, o baixo nível de polimorfismo e o reduzido número de marcas usado tem impedido uma caracterização detalhada da estrutura populacional e das relações genéticas entre os acessos dentro dos grupos gênicos (KWAK; GEPTS,…”
Section: Polimorfismos Moleculares E Diversidade Genética Em P Vulgarisunclassified